A study of 3D axis anisotropic response of MT - Liu, Xiao; Sun, Qi-Ji (Frontiers in Earth Science, 2024)
Electrical anisotropy has a significant impact on the observation data of the magnetotelluric (MT) method; therefore, it is necessary to develop forward and inverse methods in electrical anisotropic media. Based on the axis anisotropic electric field control equations, forming a large linear equation through staggered finite difference approximation, adding boundary conditions, and using the quasi-minimum residual method to solve the equation, this study obtained MT forward modeling results in axis anisotropic media. The correctness of the algorithm was verified by comparing it with the 2D quasi-analytic solution. By designing several sets of axis anisotropic 3D models, the characteristics of the apparent resistivity tensor and tipper were analyzed. The results indicated that the ρxya, ρyya and Tzy are sensitive to changes in resistivity in the X direction of the anomalous body, whereas the ρyxa, ρxxa and Tzx are sensitive to changes in resistivity in the Y direction. The apparent resistivity tensor and tipper are insensitive to changes in resistivity in the Z direction of the anomalous body. For exploration of anisotropic media, the apparent resistivity tensor and tipper of MT can identify the changes in resistivity in two horizontal axes directions and the boundaries of the anomalous body, which has the advantages for exploration.